Kenya : Participatory Poverty Assessment - World Bank (Washington, DC, 2012)
A Participatory Poverty Assessment (PPA) was undertaken by the World Bank in collaboration with the Government of Kenya to complement previous statistical studies of poverty in Kenya. While the PPA confirmed many findings of the Welfare Monitoring Survey (WMS), it also revealed significant new data concerning poverty, female-headed households, access by the poor to water, education and health facilities, and challenges facing indigenous self-help networks. These findings have import implications for targeting poverty alleviation programs.